A series of cases of rhabdomyolysis after ingestion of Tricholoma equestre - Laubner, Gabija; Mikulevičienė, Gabija (Acta medica Lituanica, 2016)
Tricholoma equestre (hereinafter – T. equestre) is a common edible fungus that is considered to be toxic under certain conditions. Here, we report four cases of acute poisoning caused by T. equestre, including one lethal outcome in Lithuania between 2004 and 2013. In the severe case, fatigue, nausea without vomiting and muscle pain, profuse sweating without fever, and respiratory insufficiency occurred. Laboratory tests showed an elevation of creatine kinase (CK), aspartate aminotransferase (AST), and alanine aminotransferase (ALT). Although clinical findings and laboratory tests support evidence of rhabdomyolysis, no renal insufficiency was observed. Significance of T. equestre in cardiac changes is feasible but remains unclear.